Satellite technology principles and applications - Maini, Anil Kumar; Agrawal, Varsha (John Wiley & Sons, 2014)
Fully updated edition of the comprehensive, single-source reference on satellite technology and its applications Covering both the technology and its applications, Satellite Technology is a concise reference on satellites for commercial, scientific and military purposes.